Green Unpleasant Land : Creative Reponses to Rural England's Colonial Connections - Fowler, Corrine (Leeds, England; Peepal Tree, 2020)
Green Unpleasant Land explores the countryside$1 (Bs repressed colonial past and demonstrates its importance as a source of ideas about Englishness. The book presents historical evidence to show that rural England was a place of conflict and global expansion. It also examines four centuries of literary response to explore how race, class, and gender have both created and deconstructed England$1 (Bs pastoral mythologies. In particular, the book argues that Black and British Asian writers have challenged narrow, nostalgic views of rural England but also expressed attachment to English landscapes and the natural world.s
English
Keywords: GF500-900 Human ecology. Anthropogeography- By region or country